Postoperative Day 1 Glucose May Be Associated With Wound Complications in Sarcomas Treated With Preoperative Radiation. Issue 3 (March 2018) - Bedi, Meena; King, David M.; Mendez, Carlos; Slawski, Barbara; Charlson, John A.; Hackbarth, Donald A.; Neilson, John C.
Abstract: Background: Uncontrolled blood glucose impacts key phases of the wound healing process. Various factors have been associated with postoperative wound complications in soft tissue sarcomas; however, the association of postoperative early morning blood glucose with wound complications, if any, remains to be determined. Because blood glucose levels may be modified, understanding whether glucose levels are associated with wound complications has potential therapeutic importance. Questions/purposes: The purposes of this study were (1) to evaluate if postoperative early morning blood glucose is associated with the development of wound complications in soft tissue sarcomas; (2) to determine a blood glucose cutoff that may be associated with an increased risk of wound complications; and (3) to evaluate if patients with diabetes have higher postoperative blood glucose and an associated increased risk of wound complications. Methods: From 2000 to 2015, 298 patients with Stage I to III soft tissue sarcomas of the extremity or chest wall were treated with preoperative radiation ± chemotherapy followed by limb-sparing resection. Of those, 191 (64%) patients had demographic, treatment, and postoperative variables and wound outcomes available; these patients' results were retrospectively evaluated. None of the 191 patients were lost to followup. Early morning blood glucose levels on postoperative day (POD) 1 were available in all patients. Wound complications were defined as those resulting in an operative procedure or prolonged wound care for 6 months postresection. Variables that may be associated with wound complications were evaluated using logistic regression for multivariate analysis. Receiver operative curve (ROC) analysis was used to assess the early morning blood glucose level that best was associated postoperative wound complications. Results: After controlling for potentially relevant confounding variables such as patient comorbidities, tumor size, and location, lower extremity soft tissue sarcomas (p = 0.002, odds ratio [OR], 6.4; 95% confidence interval [CI], 1.97-20.84) and elevated POD 1 early morning blood sugars (p < 0.001; OR, 1.1; 95% CI, 1.04-1.11) were associated with increased wound complications postoperatively. ROC analysis revealed that early morning POD 1 blood glucose of > 127 mg/dL was associated with postoperative wound complications with a sensitivity of 89% (area under the curve 0.898, p < 0.001). Median POD 1 early morning blood glucose in patients without diabetes was 118 mg/dL and 153 mg/dL in patients with diabetes (p = 0.023). However, with the numbers available, there was no increase in wound complications in patients with diabetes compared with those without it. Conclusions: Our study provides preliminary information suggesting that POD 1 early morning blood glucose in patients with soft tissue sarcomas may be associated with a slightly increased risk of postoperative wound complications. An early morning blood glucose of > 127 mg/dL may be a threshold associated with this outcome. Although patients with diabetes had higher POD 1 early morning blood glucose levels, diabetes itself was not associated with the development of wound complications. We cannot conclude that better glycemic control will reduce wound complications in patients who receive preoperative radiation, but our data suggest this should be further studied in a larger, prospective study. Level of Evidence: Level III, therapeutic study.